The Adroitness of Andrographolide as a Natural Weapon Against Colorectal Cancer - Paul, Silpita; Roy, Dia; Pati, Subhadip; Sa, Gaurisankar (Frontiers in Pharmacology, 2021)
The conventional carcinoma treatment generally encompasses the employment of radiotherapy, chemotherapy, surgery or use of cytotoxic drugs. However, recent advances in pharmacological research have divulged the importance of traditional treatments in cancer. The aim of the present review is to provide an overview of the importance of one such medicinal herb of Chinese and Indian origin: Andrographis paniculate on colorectal cancer with special emphasis on its principal bioactive component andrographolide (AGP) and its underlying mechanisms of action. AGP has long been known to possess medicinal properties. Studies led by numerous groups of researchers shed light on its molecular mechanism of action. AGP has been shown to act in a multi-faceted manner in context of colorectal cancer by targeting matrix metalloproteinase-9, Toll-like receptor or NFB signaling pathways. In this review, we highlighted the recent studies that show that AGP can act as an effective immunomodulator by harnessing effective anti-tumor immune response. Recent studies strongly recommend further research on this compound and its analogues, especially under in-vivo condition to assess its actual potential as a prospective and efficient candidate against colorectal cancer. The current review deals with the roles of this phytomedicine in context of colorectal cancer and briefly describes its perspectives to emerge as an essential anti-cancer drug candidate. Finally, we also point out the drawbacks and difficulties in administration of AGP and indicate the use of nano-formulations of this phytomedicine for better therapeutic efficacy.